Respuesta :

Answer:

(x, y) = (-1, 1)

Step-by-step explanation:

y = 2x + 3

x - y = -2 since y is equal to 2x + 3 we replace the y in the second equation with 2x + 3

x - (2x + 3) = -2 add like terms

-x - 3 = -2 add 3 to both sides

-x = 1 and x = -1

to calculate value of y we replace x with -1

y = 2x + 3

y = 2 (-1) + 3 and y = 1

Answer:

(x, y) = (-1, 1)

y = 2x + 3

x - y = -2 since y is equal to 2x + 3 we replace the y in the second equation with 2x + 3

x - (2x + 3) = -2 add like terms

-x - 3 = -2 add 3 to both sides

-x = 1 and x = -1

to calculate value of y we replace x with -1

y = 2x + 3

y = 2 (-1) + 3 and y = 1